Performance Test of Airbus A380-like using GAMA Water Tunnel and Numerical Approach - Syafria Wildan Hadi; Fauzun; Ata Syifa' Nugraha; Feri Hidayatulloh; Hijriawan, Miftah (Jurnal Rekayasa Mesin, 2025)
This study investigates the aerodynamic characteristics of the Airbus A380 model using a combination of water tunnel experimentation and Computational Fluid Dynamics (CFD) analysis. The research aims to analyze the relationship between the angle of attack (AOA) and the resulting lift and drag coefficients, providing insights into aerodynamic performance at low-speed flow conditions. Experiments were conducted using the GAMA Water Tunnel with a 1:416 scaled model of the A380. Lift and drag forces were measured using a load-cell sensor connected to an Arduino microcontroller, while CFD simulations were performed using Computational Fluid Dynamics (CFD) with the k–ω SST turbulence model. The simulation and experimental results were compared to validate the numerical approach. The findings show that both lift and drag coefficients increase with AOA up to a critical point, beyond which stall occurs at approximately 14°. The CFD results closely align with the experimental data, demonstrating strong agreement between the two methods. This research validates the reliability of water tunnel testing for aerodynamic studies and contributes to the development of cost-effective experimental methodologies for aircraft performance evaluation.